Addressing anaemia in adivasi women of reproductive age: urgent policy imperatives for Karnataka - Shriyan, Prafulla; Amruthapuri, Rahul; Kottagi, Chandrashekar; Srinivas, Prashanth N.; Babu, Giridhara R.; Seshadri, Tanya; Aggarwal, Pooja; Bhat, Deepa; Shapeti, Suresh S. (Frontiers in Global Women's Health, 2025)
The policy brief analyses program implementation gaps among Adivasi population in Southern Karnataka to support India's ‘Anemia Mukt Bharat’ and Karnataka's ‘Anemia Mukt Poushtika Karnataka’ initiatives which aims to improve anemia and nutrition status of the population This analysis is based on a Adivasi birth cohort. Preliminary results show higher underweight and anemia prevalence in Adivasi women than National Family Health Survey-5 estimates. A significant proportion of women also have thalassemia traits, suggesting a genetic predisposition. Given the burden of sickle cell disease and the undernutrition, an intersectoral approach is needed. A multistakeholder committee, including Adivasi women, experts from public health and nutrition, others are crucial to design culturally appropriate initiatives and prioritize hemoglobinopathy screening, ensuring effective strategies for this vulnerable population.